The Republic of Football Legends of the Texas High School Game - Conine, Chad S. (University of Texas Press, 2021)
Anywhere football is played, Texas is the force to reckon with. Its powerhouse programs produce the best football players in America. In The Republic of Football, Chad S. Conine vividly captures Texas's impact on the game with action-filled stories about legendary high school players, coaches, and teams from around the state and across seven decades. Drawing on dozens of interviews, Conine offers rare glimpses of the early days of some of football's biggest stars. He reveals that some players took time to achieve greatness-LaDainian Tomlinson wasn't even the featured running back on his high school team until a breakthrough game in his senior season vaulted him to the highest level of the sport-while others, like Colt McCoy, showed their first flashes of brilliance in middle school. In telling these and many other stories of players and coaches, including Hayden Fry, Spike Dykes, Bob McQueen, Lovie Smith, Art Briles, Lawrence Elkins, Warren McVea, Ray Rhodes, Dat Nguyen, Zach Thomas, Drew Brees, and Adrian Peterson, Conine spotlights the decisive moments when players caught fire and teams such as Celina, Southlake Carroll, and Converse Judson turned into Texas dynasties. Packed with never-before-told anecdotes, as well as fresh takes on the games everyone remembers, The Republic of Football is a must-read for all fans of Friday night lights